A survey of training needs for integrated medical, preventive, and managerial key personnel in primary healthcare settings in China - Ying DENG; Peilin WU; Yanqing MIAO (Zhongguo gonggong weisheng)
ObjectiveTo understand the training needs of primary healthcare professionals with integrated medical, preventive, and managerial skills, and to propose suggestions for optimizing the training of such personnel in China, providing a reference for the implementation of the "14th Five-Year Plan" for National Health. MethodsIn January 2023, a multi-stage sampling method was used to conduct a questionnaire survey on the training needs of 1 641 primary healthcare professionals from community health service centers and township hospitals in 107 prefecture-level cities (autonomous prefectures, districts/counties) across 25 provinces (autonomous regions, municipalities) in China. The survey covered four main areas: basic skills, medical skills, preventive skills, and managerial skills. ResultsAmong basic skills, the highest training need was for practicing registration qualifications, at 48.08% (789/1 641). For medical skills, the highest training need was for emergency treatment and pre-hospital first aid, at 46.62% (765/1 641). For preventive skills, the highest training need was for community health service investigation, at 45.52% (747/1 641). For managerial skills, the highest training need was for personnel training and scientific research teaching, at 51.86% (851/1 641). The lowest training need was for the implementation and management of basic public health programs, at 33.88% (556/1 641). Primary healthcare professionals in western regions and township hospitals had higher needs in all areas. ConclusionsThere are regional, urban-rural, and skill-based differences in the training needs of primary healthcare professionals with integrated medical, preventive, and managerial skills in China. It is recommended to coordinate the training of these personnel with the development of village (community) public health committees, clarify their corresponding skill development requirements, and accelerate the standardization process.